The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-66944-4
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Equine arteritis virus is efficiently suppressed by purine and pyrimidine biosynthesis inhibitors

Abstract: RNA viruses are responsible for a large variety of animal infections. Equine Arteritis Virus (EAV) is a positive single-stranded RNA virus member of the family Arteriviridae from the order Nidovirales like the Coronaviridae. EAV causes respiratory and reproductive diseases in equids. Although two vaccines are available, the vaccination coverage of the equine population is largely insufficient to prevent new EAV outbreaks around the world. In this study, we present a high-throughput in vitro assay suitable for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, the upregulation of some enzymes in this pathway indicates a poor prognosis in cancer patients, hence these genes are attractive anticancer drugs to inhibit proliferation and metastasis [ 16 , 17 , 18 , 19 ]. Likewise, viral replication relies on the host to supply nucleotides, thus the enzymes in this pathway are targets for antiviral treatments [ 20 , 21 , 22 , 23 ]. Moreover, the inhibition of pyrimidine biosynthesis enzymes is employed for the treatment of microorganism and parasite infections [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the upregulation of some enzymes in this pathway indicates a poor prognosis in cancer patients, hence these genes are attractive anticancer drugs to inhibit proliferation and metastasis [ 16 , 17 , 18 , 19 ]. Likewise, viral replication relies on the host to supply nucleotides, thus the enzymes in this pathway are targets for antiviral treatments [ 20 , 21 , 22 , 23 ]. Moreover, the inhibition of pyrimidine biosynthesis enzymes is employed for the treatment of microorganism and parasite infections [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antiviral activity of direct-acting and host-directed antivirals has generally been evidenced using cell lines of rodent or primate origin, models that may be poorly predictive of therapeutic efficacy in horses. Equine dermal cells (ED) have been used to test antivirals against equine arteritis virus [9] and equine herpes virus [10], but are unsuitable for study of WNV as they are weakly permissive to WNV (personal observation). Equine brain cells would represent a more relevant model, as WNV disease results from brain infection.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that some viruses enhance the synthesis of nucleotides to facilitate replication [28][29][30] . Earlier research has demonstrated that VACV replication was reduced when treated with N-phosphonacetyl-L-aspartate (PALA), an inhibitor of the de novo pyrimidine pathway 31 .…”
Section: Introductionmentioning
confidence: 99%